USING MIND-MAPPING TO IMPROVE READING COMPREHENSION AND WRITING ACHIEVEMENTS OF THE 4TH SEMESTER STUDENTS OF STAIN CURUP - Melli Kusmaningrum (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
Abstract: This research was aimed to find out whether or not there was a significant improvement in students’ reading comprehension and writing achievements after they were taught by using Mind-mapping and there were significant differences in reading comprehension and writing achievements between the students who were taught by using mind-mapping and those who were not. This research also aimed to know the students’ feedback about the use of mind-mapping in learning reading and writing. A quasi experimental method was applied in this research. There were 40 fourth semester students of English Education Study Program of STAIN Curup selected as the sample by using a purposive sampling technique. They were divided into experimental and control groups equally. The data were collected by using a reading comprehension test, a writing test, and a questionnaire. The results of the tests were analyzed quantitatively by using independent and paired sample t-tests and the results of the questionnaire were analyzed quantitatively by using simple percentage analysis and described qualitatively as well. The results of this research showed that there was a significant improvement in students’ reading comprehension and writing achievements and there were also significant differences in reading comprehension and writing achievements between the students who were taught by using mind-mapping and those who were not. The students also showed positive feedback towards the use of mind-mapping. In conclusion, mind-mapping could improve the students’ reading and writing achievement. Keywords: Reading comprehension, writing achievement, mind-mapping